Faktor-Faktor yang Mempengaruhi Kemiskinan di Desa Kondamara Kecamatan Lewa - Yowa, Meliani Koku; Hudang, Adrianus Kabubu; Renggo, Yuniarti Reny (LPPM Institut Pendidikan Nusantara Global, 2024)
Poverty is a complex problem caused by many interrelated factors. So, this research will analyse the variables that influence poverty in Kondamara Village, Lewa District by analysing important problems that can influence poverty. This research aims to determine the profile and factors that influence poverty in Kondamara Village, Lewa District. The data collection technique uses primary data obtained through distributing questionnaires and direct interviews with poor and non-poor households in Kondamara Village, Lewa District. Meanwhile, the data analysis technique uses binary logistic regression analysis with a Likelihood Ratio approach. The research results show that the income of the head of the household and the number of family dependents have a significant influence on poverty in Kondamara Village, Lewa District.